2021
DOI: 10.1093/plcell/koab045
|View full text |Cite
|
Sign up to set email alerts
|

ATM controls meiotic DNA double-strand break formation and recombination and affects synaptonemal complex organization in plants

Abstract: Meiosis is a specialized cell division that gives rise to genetically distinct gametic cells. Meiosis relies on the tightly controlled formation of DNA double-strand breaks (DSBs) and their repair via homologous recombination for correct chromosome segregation. Like all forms of DNA damage, meiotic DSBs are potentially harmful and their formation activates an elaborate response to inhibit excessive DNA break formation and ensure successful repair. Previous studies established the protein kinase ATM as a DSB se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 129 publications
8
59
0
Order By: Relevance
“…Each single focus found at an epifluorescence microscope is composed of several smaller foci at the STED (compare RAD51 staining in Figures 2, 5). While RAD51 foci, for example, were found to be mainly circular and peak in zygotene at around 200 foci per nucleus in widefield images (Kumar et al, 2019;Sims et al, 2019;Kurzbauer et al, 2021), more than 1,000 foci are found in images acquired by STED nanoscopy (Figure 5). In addition, foci seem to assume different shapes over time, with few larger clusters forming in pachytene and likely representing different repair intermediates.…”
Section: Meiotic Repair Proteins and Colocalization Of Complex Partnersmentioning
confidence: 99%
See 3 more Smart Citations
“…Each single focus found at an epifluorescence microscope is composed of several smaller foci at the STED (compare RAD51 staining in Figures 2, 5). While RAD51 foci, for example, were found to be mainly circular and peak in zygotene at around 200 foci per nucleus in widefield images (Kumar et al, 2019;Sims et al, 2019;Kurzbauer et al, 2021), more than 1,000 foci are found in images acquired by STED nanoscopy (Figure 5). In addition, foci seem to assume different shapes over time, with few larger clusters forming in pachytene and likely representing different repair intermediates.…”
Section: Meiotic Repair Proteins and Colocalization Of Complex Partnersmentioning
confidence: 99%
“…These two stages are highly informative, because chromosome fragments are visible when DNA repair is defective (as in com1-1 , Figures 1G2 , H2 ) and chromosome missegregation can be observed when homolog interactions are reduced or absent (as in spo11-2-3 ; Figures 1G1 , H1 ; Grelon et al, 2001 ; Stacey et al, 2006 ). In addition, irregular repair might manifest in chromatin bridges, well visible during these (and subsequent) stages ( Figures 1H2 , L2 ; Uanschou et al, 2007 ; Kurzbauer et al, 2021 ) and cohesion-deficiencies may result in premature sister separation ( Cai et al, 2003 ; Chelysheva et al, 2005 ).…”
Section: Meiotic Stages (Observed Under the Widefield Microscope)mentioning
confidence: 99%
See 2 more Smart Citations
“…The number of meiotic DSBs per cell must be carefully titrated to ensure sufficient DSB formation for successful meiotic recombination while minimizing the risk of chromosome abnormalities associated with excessive DSB numbers. ATM mutants in various organisms exhibit increased DSB formation, suggesting a universal role for ATM in the regulation of DSB levels (Joyce et al, 2011;Lange et al, 2011;Checchi et al, 2014;Garcia et al, 2015;Mohibullah and Keeney, 2017;Fowler et al, 2018;Kurzbauer et al, 2021). In S. cerevisiae and S. pombe, ATM regulates DSB numbers by preventing double-cutting in proximity of DSBs (Garcia et al, 2015;Fowler et al, 2018).…”
Section: Control Of Dsb Numbersmentioning
confidence: 99%